O conflito ideológico no discurso sobre a maconha: uma abordagem dialógica de matérias impressas veiculadas na mídia brasileira - Silva, Carolina Gonçalves da [UNESP] (2013)
According to data published on the World Drug Report 2012 by Unodc - United Nations Office on Drugs and Crime -, the world consumes nowadays the same amount of illicit drugs that it has always consumed. Contrary to this stable consumption, discussions surrounding the issue of drugs have intensified. The greatest controversies and the largest repercussion in the Brazilian media relate to marijuana use. This paper was developed in the context of polemic issues and its general goal is to analyze the conflict of ideologies present in the discourses about drugs on printed articles released by the Brazilian media, represented here by the magazines Veja, Carta Capital and Galileu. This study is carried out based on a dialogic approach, supported by the Bakhtinian researches on discourse